Determinantes del estrés académico y su impacto en el rendimiento estudiantil. - Suquisupa Alvarado, Celina Leonela; Ahuananchi Añazco, Yulissa Dayana (My University, 2024)
This study addresses academic stress and its impact on the performance of Nursing students at a public university in Machala, Ecuador. Through a quantitative, descriptive, and cross-sectional design, a validated survey was applied to a sample of 158 officially enrolled students. The objective was to identify the main sources, manifestations, and coping strategies related to academic stress, as well as its relationship with sociodemographic variables and academic performance. The findings revealed a high prevalence of stress, with the primary stressors being academic workload, frequent evaluations, and difficulty balancing personal and academic responsibilities. The most common manifestations included anxiety (35.4%), insomnia (14.6%), and nervousness (12.6%), alongside physical symptoms such as gastrointestinal problems and changes in appetite. The analysis showed that female students reported higher levels of stress and used fewer effective coping strategies, such as relaxation techniques or seeking academic support from faculty. Despite this, most students rated their overall academic performance as "good," though they reported challenges in content comprehension, teamwork, and time management. Alarmingly, 35.4% of participants considered dropping out due to academic stress. The study concludes that academic stress has a significant negative impact on students’ physical and mental health, as well as their academic performance. Therefore, it is essential for higher education institutions to implement psychoeducational support programs and preventive strategies. Additionally, notable differences were identified based on gender and marital status, highlighting the need for tailored interventions to reduce stress and promote academic success among nursing students.
El presente estudio aborda el estrés académico y su repercusión en el rendimiento de estudiantes de Enfermería de una universidad pública en Machala, Ecuador. A través de un diseño cuantitativo, descriptivo y transversal, se aplicó una encuesta validada por expertos a una muestra de 158 estudiantes legalmente matriculados, con el objetivo de identificar las principales fuentes, manifestaciones y estrategias de afrontamiento del estrés, así como su relación con variables sociodemográficas y el rendimiento académico. Los resultados revelaron una alta prevalencia de estrés, destacando como principales factores la carga académica, las evaluaciones frecuentes y la dificultad para equilibrar responsabilidades personales y académicas. Las manifestaciones más comunes fueron ansiedad (35.4 %), insomnio (14.6 %) y nerviosismo (12.6 %), acompañadas de síntomas físicos como problemas gastrointestinales y cambios en el apetito. El análisis mostró que las mujeres presentan niveles más elevados de estrés y menor uso de estrategias efectivas de afrontamiento como la relajación o el apoyo académico docente. Pese a ello, la mayoría calificó su rendimiento como “bueno”, aunque con dificultades en comprensión de contenidos, trabajo en equipo y gestión del tiempo. Alarmantemente, el 35.4 % consideró abandonar la carrera por estrés. Se concluye que el estrés académico impacta negativamente en la salud física, mental y desempeño académico de los estudiantes, siendo crucial que las instituciones implementen programas de apoyo psicoeducativo y estrategias preventivas. Asimismo, se identificaron diferencias relevantes según sexo y estado civil, lo que sugiere la necesidad de intervenciones personalizadas para mitigar el estrés y fortalecer el éxito académico.
Keywords: ESTRÉS ACADÉMICO; ESTUDIANTES DE ENFERMERÍA; RENDIMIENTO ACADÉMICO